Kajian Akulturasi Pada Aspek Intramusikal Dalam Komposisi Musik Program “Watu Pinawetengan” - Yudi Novrian Komalig (SELONDING, 2018)
Music as part of culture is always changing. These changes can occur due to several things, one of them through acculturation. Acculturation is the intercultural contact of culturally intercultural groups that leads to cultural change for the group.Acculturation can be seen in a musical genre that combines two cultural idioms. One of them is the musical composition of Watu Pinawetengan program which will be described in this article. The composition of Watu Pinawetengan music program is a music program with string quartet format and instrument of tambur (percussion instrument of Minahasa). This musical composition consists of three movements, where each movement is inspired from Minahasa folklore about the origin of the division of agricultural areas. The first movement tells the story of the daily life of the Minahasan people. The second move tells the story of the conflict that occurred in the fight over agricultural land. While the third movement tells about negotiations to resolve conflicts in the division of agricultural areas.The musical composition of the program combines the ethical idioms of Minahasa music and western music. These idioms are manifested in the intramusic aspect, whether they are realized as melodies or harmonies. The merging of these two idioms will result in an acculturation. This acculturation process will be described in this article. What intramusical aspects are acculturated, the extent to which acculturation causes change, and which culture is stronger in its influence on other cultures. Keywords: Music, Composition.